Ultrasonic vibration-assisted (UV-A) manufacturing processes: State of the art and future perspectives. (March 2020) - Ning, Fuda; Cong, Weilong
Abstract: In recent years, ultrasonic technology has been extensively applied in numerous manufacturing processes to improve the process performance and part quality. This review paper presents a broad overview on the recent progress in ultrasonic vibration-assisted (UV-A) manufacturing processes reported in the literature. Based on the ultrasonic energy propagation through solid or liquid phases, UV-A manufacturing processes can be divided into mechanical manufacturing processes (including conventional machining, densification, forming, and consolidation) and thermal manufacturing processes (including thermal non-traditional machining, casting, fusion welding, laser cladding, and direct laser deposition). The results from a great number of published investigations have strongly evidenced the significant influences of ultrasonic vibration during the material processing. In UV-A mechanical manufacturing processes, ultrasonic vibration can reduce the machining force through intermittent cutting between machine tools and the workpiece, decrease the load in both densification and forming processes due to the reduced friction, and increase the bond at the workpiece interface by breaking oxide layers in ultrasonic consolidation. In UV-A thermal manufacturing processes, on the other hand, ultrasonic vibration can exert nonlinear effects (acoustic streaming and cavitation) on the solidification behavior of liquid melting materials. The precision and quality of parts fabricated by thermal manufacturing will be thus improved through various phenomena such as element homogenization, material degassing, crack reduction, microstructure refinement, etc. This literature review aims to provide a comprehensive overview on ultrasonic vibration influences in different UV-A manufacturing processes and guide the future development of ultrasonic vibration assisted technologies.